MULTIVARIATE ANALYSIS FOR EVALUATION THE WATER QUALITY OF TIGRIS RIVER WITHIN BAGHDAD CITY IN IRAQ - & et al., Al-Ani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study is to evaluate the water quality of Tigris river by measuring the physicochemical parameters of the river within Baghdad city in Iraq from the period of February 2017 to February 2018. Four sites were selected from upreach, reach and downreach. Temperature of air and water, pH, electrical conductivity, salinity and water flow were measured in the field, While, the laboratory measurements included total dissolved substances (TDS), total suspended substances (TSS), turbidity, nutrients (nitrite, nitrate and phosphate), biochemical oxygen demand (BOD), chemical oxygen demand (COD), dissolved oxygen (DO), organic matter and total organic carbon (TOC), these parameters were used to indicate the pollution of Tigris River ecosystem. The results show that all parameters variation in both seasons (wet and dry), which has led to a deterioration in water quality. A higher level of contamination was recorded at reach sites (Al-Sarrafia Bridge and Al-Shuhada Bridge) in contrast to other sites (Al-Muthanna Bridge and Al-Dora Bridge). This indicates that the Tigris river in the middle of Baghdad city is more polluted due to the anthropogenic impacts.